National law and legal pluralism - S. V. Biryukov (Правоприменение, 2022)
The subject of the article is correspondence and competition legal monism and legal pluralism. The purpose of the study is to confirm or refute the author's hypothesis that a peculiar dialectic of legal monism and legal pluralism is inherent in domestic law.The methodology. The methods of various sciences related to the study of social and legal pluralism are combined. In particular, the system approach, dialectical method, methods of formal logic, formal-legal and comparative-legal methods, theoretical-sociological and theoretical-cultural analysis are used.The main results, scopresue of application. Within the framework of various social sciences, types of legal understanding, both a monistic view of law and various opinions about its plurality are presented (natural and positive law; the law of various states; domestic and international law; official and unofficial law).Domestic law in developed countriesis unified, but it is a complex unity consisting of various subsystems (levels). The question of whether these subsystems can not only correspond to each other and complement each other, but also compete with each other, be used by various entities within the framework of choosing the optimal regime of legal regulation has always been ambiguousfor lawyers.Discussions about legal monism and legal pluralism contribute to the development of theoretical knowledge about law. Situations of more or less pronounced legal plurality undoubtedly influence the specifics of all the main types of legal activity: from legal education and criticism of law to law enforcement. For the latter, the problem of compatibility of the principles of legality, formal equality and various forms of legal plurality has always been one of the most important.Conclusions. The main manifestations of weak legal pluralism in modern domestic law can be considered as: (1) identification of subsystems of the law of the subjects of the federation and municipalities; (2) recognition of partial legal autonomy of various non-public organizations and autonomous communities (mainly in the field of private law). Each of these manifestations is considered separately. The problem of constitutionalization of legal pluralism is also touched upon. It is shown that a peculiar dialectic of legal monism and legal pluralism isinherent in domestic law.